Thorns in the side: Strategies of populist parties against local public administrations - Eliska Drapalova (Governance, 2024)
The success of populist parties in national elections puts pressure on political leaders and their administrations, both at the central and sub-national levels. This paper explores the political tensions between two administrative levels—a central level governed by a populist party, and the city level headed by a liberal party—and the strategies populists use to challenge local political leaders and their city administrations. This paper analyzes three case studies: Prague, Warsaw, and Budapest. In all three cities, opposition candidates are visible challengers to the populist parties in government. The results show that city administrations face increasing tasks, cuts in budget transfers, higher scrutiny from central government, and administrative bottlenecks.
Keywords: 320